1126 Relationship Between Headache and Sleep: A Longitudinal Study from the Population of Sao Paulo City (Brazil). (27th May 2020) - Lucchesi, L M; Tempaku, P F; Smith, A A; Togeiro, S; Hachul, H; Andersen, M; Tufik, S; Poyares, D
Abstract: Introduction: The complaint of nocturnal awakening with headache (NAH), was prevalent (8.4%) in the São Paulo population and was associated with sleep disturbances, as demonstrated in a study conducted in 2007 (EPISONO). Indeed, this relationship between sleep and headache is well documented in the literature. Objective: To assess the incidence and evolution of NAH and to associate sleep-related variables in an eight-year prospective study. Methods: From 1042 volunteers enrolled in the baseline, 712 agreed to participate in the follow-up. Questionnaires and scales were applied and polysomnography and actigraphy performed. The complaint of NAH was analyzed according to a frequency questionnaire and separated into frequent or occasional. Results: At follow-up, 110 volunteers reported NAH, of which 82 were the same as those from the baseline, but only 38 had frequent complaints. Comparing with volunteers whose headache has become occasional, we have as a difference the insomnia severity index which is significantly higher in the group with frequent NAH (8.40 ± 5.10 vs 11.20±6.40 p:0.03) and worse sleep quality as measured by the Pittsburgh questionnaire (7.25±3.60 vs 10.25±4.60 p:0.002). In addition, these volunteers had higher anxiety (10.40±9.30 vs 12.00± 10:00 p: 0.008) and depression (10.60±9.90 vs 12:00±9.90 p:0.005) from Beck's questionnaires and greater fatigue (4.85±3.10 vs 9.75±5.55 p:0.001). The associations of NAH with insomnia, nightmares, and bruxism observed in the baseline continued, but no difference was observed between those who had frequent or occasional complaints at follow-up. Conclusion: Our study showed that NAH was highly prevalent in the Sao Paulo population in both the baseline and follow-up studies, but this frequency had a reduction in follow-up. Volunteers who persisted with the frequent complaint showed greater severity of insomnia, higher anxiety and depression and greater fatigue. Support: Associação Fundo de Incentivo à Pesquisa (AFIP) and São Paulo Research Foundation (FAPESP)